Knowledge mapping of image-guided tumor ablation and immunity: A bibliometric analysis - Shen, Hui; Wang, Lin; Zhang, Yi; Huang, Guangliang; Liu, Baoxian (Frontiers in Immunology, 2023)
Background: Various ablation techniques have been successfully applied in tumor therapy by locally destroying tumor. In the process of tumor ablation, a large number of tumor cell debris is released, which can be used as a source of tumor antigens and trigger a series of immune responses. With the deepening of the research on the immune microenvironment and immunotherapy, research exploring tumor ablation and immunity is continuously published. However, no research has systematically analyzed the intellectual landscape and emerging trends for tumor ablation and immunity using scientometric analysis. Therefore, this study aims to conduct a bibliometric analysis to quantify and identify the status quo and trend of tumor ablation and immunity. Methods：Data of publications were downloaded from the Web of Science Core Collection WoSCC database. CiteSpace and VOSviewer were used to conduct bibliometric analysis to evaluate the contribution and co-occurrence relationship of different countries/regions, institutions and authors in the field, and to determine the research hotspots in this field. Results: By searching in the database, a total of 3531 English articles published between 2012 and 2021 were obtained. We observed rapid growth in the number of publications since 2012. The two most active countries are China and the United States, with more than 1,000 articles. Chinese Academy of Sciences contributed the most publications (n = 153). Jibing Chen and Xianzheng Zhang may have a keen interest in tumor ablation and immunity, with more publications (n = 14; n = 13). Among the top 10 co-cited authors, Castano AP (284 citations) was ranked first, followed by Agostinis P (270 citations) and Chen Qian (246 citations). According to the co-occurrence and cluster analysis, the results indicated that the focus of research is “photothermal therapy”, “hypoxia”, and “immune checkpoint blockade”. Conclusions: In the past decade, the neighborhood of tumor ablation domain immunity has been paid more and more attention. Nowadays, the research hotspots in this field are mainly focused on exploring the immunological mechanism in photothermal therapy to improve its efficacy, the combination of ablation therapy and immune checkpoint inhibitor therapy,and investigating the role of hypoxia in tumor ablation.